Movements After Revolution : A History of People's Struggles in Mexico - Rodríguez, Miles V. (Book collections on Project MUSE., 2022)
"Movements After Revolution is a history of how and why people's movements organized and struggled in the aftermath of the Mexican Revolution of 1910-20. Focusing on the first decade after the Revolution in 1920-30, it explains the rise of an unprecedented variety of organizations among industrial workers and rural communities, and how they fought for a vast array of demands and diverse forms of justice. The most independent and strategic parts of the labor movement and the agrarian movement grew in relation to Communist organizers who sought to create a national revolutionary alliance against capitalism and the state, as part of an international revolutionary movement for socialism. In response to national crises and changes in global revolutionary strategy, these parts of the labor movement and the agrarian movement formed unique allied organizations and prepared for ultimately ruinous struggles with companies, landlords, and the state. By examining the roles of activists, their antagonists, divisive contexts, and complex consequences, this work offers original insights into the influences and limits of the Revolution on people's movements in Mexico"--